Three-dimensional printing of mitral valve models using echocardiographic data improves the knowledge of cardiology fellow physicians in training - Bulbul, Ziad; El Rassi, Issam; Hamade, Ramsey; Tamim, Hani; Bitar, Fadi (Frontiers in Cardiovascular Medicine, 2023)
Background: High fidelity three-dimensional Mitral valve models (3D MVM) printed from echocardiography are currently being used in preparation for surgical repair. Aim: We hypothesize that printed 3DMVM could have relevance to cardiologists in training by improving their understanding of normal anatomy and pathology. Methods: Sixteen fellow physicians in pediatric and adult cardiology training were recruited. 3D echocardiography (3DE) video clips of 6 mitral valves (one normal and five pathological) were displayed and the fellows were asked to name the prolapsing segments in each. Following that, three still images of 3D MVMs in different projections: enface, profile and tilted corresponding to the same MVs seen in the clip were presented on a screen. Participating physicians were presented with a comprehensive questionnaire aimed at assessing whether the 3D MVM has improved their understanding of valvular anatomy. Finally, a printed 3D MVM of each of the valves was handed out, and the same questionnaire was re-administered to identify any further improvement in the participants’ perception of the anatomy. Results: The correct diagnosis using the echocardiography video clip of the Mitral valve was attained by 45% of the study participants. Both pediatric and adult trainees, regardless of the year of training demonstrated improved understanding of the anatomy of MV’s after observing the corresponding latter’s model image. Significant improvement in their understanding was noted after participants had seen and physically examined the printed model was noted. Conclusion: Printed 3D MVM has a beneficial impact on the cardiology trainees’ understanding of MV anatomy and pathology compared to 3DE